2016
DOI: 10.3233/wor-162410
|View full text |Cite
|
Sign up to set email alerts
|

Uprising: An examination of sit-stand workstations, mental health and work ability in sedentary office workers, in Western Australia

Abstract: Abstract. BACKGROUND:Office-based staff spend around three quarters of their work day sitting. People who sit for long periods while at work are at greater risk of adverse health outcomes. OBJECTIVE: The pilot study aimed to determine the effect of sit-stand workstations on office-based staff sedentary and physical activity behaviors, work ability and self-reported physical and mental health outcomes. METHODS: A two-group pre-post study design assessed changes in sedentary and physical activity behaviors (time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 24 publications
2
36
1
Order By: Relevance
“…Using an accelerometer van Dommelen [12] recorded white collar workers sitting for between 76-80% of their occupational time. The results from these studies [12,29,36] support the baseline of normal sitting and standing patterns at work.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Using an accelerometer van Dommelen [12] recorded white collar workers sitting for between 76-80% of their occupational time. The results from these studies [12,29,36] support the baseline of normal sitting and standing patterns at work.…”
Section: Introductionsupporting
confidence: 62%
“…However, in an observational study of office and leisure activity, Thorp et al [29] reported 77% of working hours were sedentary, which left up to 23% of work time not sitting, without any intervention. Tobin et al [36] reported the same measurements as Thorp et al [29] at baseline before the introduction of an adjustable workstation. Ryan et al [43] measured sitting patterns at work and reported a mean of 66% (SD 12%) of the working day was spent sitting.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…In recent years there has been increasing interest in understanding the efficacy of a broad range of interventions targeting workplace sitting [5]. Sit-stand workstations, which facilitate postural shifts from sitting to standing and vice versa throughout the day, have been shown to be an effective environmental-based tool, leading to moderate to large reductions in sitting time [6, 7] with minimal or no impacts on productivity or work performance [8–10]. However, evidence reviews have suggested that greater impacts on workplace sitting may be achieved if sit-stand workstations are implemented as part of a broader approach that addresses the multiple levels of influence on behaviour [5, 11, 12].…”
Section: Introductionmentioning
confidence: 99%